Recommendations for management of diabetic foot ulcers during COVID-19 outbreak. - KELAHMETOĞLU, OSMAN; Kelahmetoglu, Osman; ERGÜN, SELMA; Camlı, Mf; GÜNEREN, ETHEM; Kirazoglu, A; Erbayat, Y; Guneren, E; Asgarzade, S; Durgun, U; Mehdizade, T; Yeniocak, A; et al. (My University, 2020)
COVID-19 pandemia began in Wuhan, China, in December 2019. A total of 1 878 489 people were infected and 119 044 people were lost because of the disease and its complications by 15 April. Severe morbidity and mortality complications are mostly seen in elderly and patients having comorbidities. Diabetic foot ulcers (DFUs) are one of severe complications of diabetes mellitus and it may require urgent surgical interventions. In this paper, we aimed to create a management algorithm to prevent the unexpected complications that may occur in the patients and health care workers during the evaluation of COVID-19 in DFU patients who require urgent surgical intervention. We advise the use of thorax computerised tomography for preoperative screening in all DFU patients with severe signs of infection and especially those requiring urgent surgery for both the detection of the possible undiagnosed COVID-19 in the patient for the need for close follow-up and protection of the surgical and anaesthesiology team.
Keywords: COVID-19; Diabetic foot; Ulcer; Urgent